2021
DOI: 10.3201/eid2710.211394
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 and Pregnancy Outcomes According to Gestational Age at Time of Infection

Abstract: We conducted an international multicenter retrospective cohort study, PregOuTCOV, to examine the effect of gestational age at time of infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) on obstetric and neonatal outcomes. We included all singleton pregnancies with a live fetus at 10 weeks’ gestation in which pregnancy outcomes were known. The exposed group consisted of patients infected with SARS-CoV-2, whereas the unexposed group consisted of all remaining patients during the same peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 32 publications
3
37
0
3
Order By: Relevance
“…The observation that maternal infections affect the pregnancy outcome by resulting in miscarriage, preterm birth, fetal malformations or enhanced risk for pregnancy complications, e.g. in the context of HCMV, ZIKV, and COVID19 infections (111)(112)(113)(114) highlights the urgent need for further research in this field.…”
Section: Immune Surveillance and Host Defensementioning
confidence: 99%
“…The observation that maternal infections affect the pregnancy outcome by resulting in miscarriage, preterm birth, fetal malformations or enhanced risk for pregnancy complications, e.g. in the context of HCMV, ZIKV, and COVID19 infections (111)(112)(113)(114) highlights the urgent need for further research in this field.…”
Section: Immune Surveillance and Host Defensementioning
confidence: 99%
“…Although some studies suggested higher rates of SARS-CoV-2 infection in pregnant women compared with adults of reproductive age, understanding the extent to which this reflects differences in exposure risk, threshold for investigating and rate of testing, rather than a genuine increase in susceptibility remains a challenge. Nevertheless, the growing evidence demonstrates an increased risk of severe adverse outcomes from SARS-CoV-2 infection in pregnant compared with non- pregnant women, particularly when infection occurs during late-second and early-third trimesters ( 11 , 12 ). This increased burden of COVID-19 appears to be disproportionately affecting mother-neonate dyads from low- and middle- income countries ( 13 ).…”
Section: Incidence and Burden Of Covid-19 In Pregnant Womenmentioning
confidence: 99%
“…Although a systematic review reported from four studies that risk was not increased in the third trimester (n = 29), 1 other studies have reported increased prevalence of symptomatic 4 and severe infection in the later stages of pregnancy. 3,5 A high proportion (17%) of women with COVID-19 in pregnancy are reported to have a preterm birth (<37 weeks of pregnancy), which reflects nearly a 50% increase compared with those without COVID-19 (OR 1.47), 1 and the odds of their baby being admitted to a neonatal unit (NNU) are also increased (OR 4.89). 1 Evidence from subsequent small studies suggests that women with severe illness are more likely to have a preterm birth (41.8% vs 15.2%, 2 45.4% vs 5.2% 3 ) and their babies more likely to be admitted to neonatal units (NNU, ie intensive or specialist care) than those with mild illness (50.4% vs 19.2%).…”
Section: Introductionmentioning
confidence: 99%